FEATURES OF THE MODERN METHOD OF TRAINING GUS (EDUCATION IN THE 21ST CENTURY, 2023)
"Teaching of the modern method of GUS teaching"to try in the article "characteristics of communication".to show different approaches to using the method, depending on the teachingdepending on the nature of the material and the age group of the students. Application of the methodWe have made visible the unique features of Armenian literature.based on the analysis of literary works included in the school curriculumon.
Keywords: visual memory, comparative-analytical thinking, ideological problems, imagery.